A reorganização da matemática escolar do colégio em tempos do Movimento da Matemática Moderna - Silva, Givanildo Farias da (2008)
The target of this work is investigating the change s process that School Mathematic for Secondary School, nowadays High School, during decades of 1950 and 1960. This target was gained on through legislation on the time, as Programas do Ensino Secundário, laid out by Portaria 966 on the 2nd of October 1951, the Law 4024/61 that created the Diretrizes e Bases da Educação Nacional besides Sugestões para um roteiro de Programa para a cadeira de Matemática proposed by GEEM in 1965. It had used set of didactic books Matemática Curso Colegial Moderno, by Scipione Di Pierro Neto, Luiz Mauro Rocha and Ruy Madsen Barbosa, published on time of Modern Mathematic s Movement that have been considered at first hand publishing in this period to High School. To substantiate these analyses, it was used the contribution by André Chervel (1990) with the History of School Subjects and Alain Choppin (2004) he have searched and to reflect about didactic books and he have consided these books a complex production. Like this, it is possible to observe the changes on the introduction of the subjects that it would be taught on High School ever since Portaria de 51 even Sugestões by GEEM, in 1965, besides assimilation these Sugestões on set Matemática Curso Colegial Moderno. However, the main change had been a new language for content s introduction begining from Teory of Conjunct, from Logical and from Algebraical Structures, besides incorporation of news contents, as Matrix, Transformation s Geometry, Probability and an analyse by elementary and trigonometricals Function and Analitic Geometry